2003
DOI: 10.1002/app.2379
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the free volume in high‐impact polystyrene/polypropylene and high‐impact polystyrene/high‐density polyethylene blends probed by positron annihilation spectroscopy

Abstract: ABSTRACT:The free-volume properties of high-impact polystyrene (HIPS)/polypropylene (PP) and HIPS/highdensity polyethylene (HDPE) blends were investigated by means of positron annihilation lifetime spectroscopy (PALS). The measured results show that the free-volume holes in the semicrystalline polymers, such as PP and HDPE, were not large enough to accommodate the branched chains and the end groups of the macromolecular chains in HIPS to produce favorable interactions between the semicrystalline polymers and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…It has been reported that as the alkyl branches of α‐olefins are increased, there is an increase in the amorphous phase free volume and in the interfacial surface area, leading to plasticization 38–40. Qi et al41 showed that the free‐volume holes in semicrystalline polymers (e.g., polypropylene and high‐density polyethylene) are not large enough to accommodate the branched chains and end groups of the macromolecular chains in high‐impact polystyrene (HIPS) to produce favorable interactions between the semicrystalline polymers and the HIPS polymer, and thus immiscible blends are formed. As the filler size decreases, the interfacial area between the fillers and the polymer matrix increases dramatically; the increasing interfacial area can influence the chain mobility and results in a depression of T g .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that as the alkyl branches of α‐olefins are increased, there is an increase in the amorphous phase free volume and in the interfacial surface area, leading to plasticization 38–40. Qi et al41 showed that the free‐volume holes in semicrystalline polymers (e.g., polypropylene and high‐density polyethylene) are not large enough to accommodate the branched chains and end groups of the macromolecular chains in high‐impact polystyrene (HIPS) to produce favorable interactions between the semicrystalline polymers and the HIPS polymer, and thus immiscible blends are formed. As the filler size decreases, the interfacial area between the fillers and the polymer matrix increases dramatically; the increasing interfacial area can influence the chain mobility and results in a depression of T g .…”
Section: Resultsmentioning
confidence: 99%
“…The free‐volume size in the polypropylene molecules is not sufficiently large to accommodate the large and rigid diamondoid molecules. As the alkyl branches of α‐olefins are increased, there is an increase in the free volume in the amorphous phase and interfacial surface area, leading to the plasticization 38–41…”
Section: Discussionmentioning
confidence: 99%
“…The longest lived component of the positron lifetime spectra, τ 3 , and the corresponding o ‐Ps intensity, I 3 , are correlated with the mean radius ( R ) and the relative number of free volume cavities in the polymer material, respectively. A mixture of polymers with different structures of lateral groups and condensed states usually results in an obvious change in blend properties of the polymers . Results (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been considered that such kind of impurities or contaminant would affect the mechanical properties deteriorate of the recycled plastic materials, however, quantitative investigations on the validity of contamination in order to use the recycled material as the desired performance has not been conducted sufficiently. 2,[7][8][9][10] In OA equipments, casing plastic materials often contact with gear wheal, at that place, grease is commonly used in order to avoid abrasion by friction. As the result, the recycled plastic casing is possibly adhered with grease, and it is difficult to remove the grease because of its high viscosity.…”
Section: Introductionmentioning
confidence: 99%